Decision-making styles during stressful scenarios: The role of anxiety in COVID-19 pandemic - Marques da Rocha, Mariana Castro; Malloy-Diniz, Leandro Fernandes; Romano-Silva, Marco Aurélio; Joaquim, Rui Mateus; Serpa, Alexandre Luiz de Oliveira; Paim Diaz, Alexandre; de Paula, Jonas Jardim; Costa, Danielle Souza; Silva, Antônio Geraldo da; Pinto, André Luiz de Carvalho Braule; de Miranda, Débora Marques (Frontiers in Psychiatry, 2023)
Introduction: Decision-making is not purely rational but highlighted by the influence of intuitive and emotional processes. Recently, researchers have focused more attention on understanding which environmental and personal features influence decision-making processes, and how. Objective and Methods: On this study, we investigate whether Trait Anxiety moderates the impact of Post-Traumatic Stress (PTS) symptoms reported during COVID-19 pandemic on decision-making styles. Results: The study included 1358 Brazilian participants (80% women) aged between 20 and 74 (M=41.11; SD=11.23) who responded to an online survey during month of the year 2021 of COVID-19 pandemic to the State-Trait Anxiety Inventory, Decision Style Scale, Impact of Event Scale – Revised and questions related to COVID-19. Through moderation analysis, we observed that experiencing PTS is associated with a higher tendency to biased/heuristic decision-making processes. Discussion: Trait Anxiety seems to influence how people respond to PTS symptoms on decision-making related processes. Subjects with higher Trait Anxiety reported lower tendency to appeal to rationality, especially under higher reported levels of PTS. Meanwhile, lower Trait Anxiety subjects exhibited more reason-based decision-making under higher rates of PTS. This work contributes to a deeper understanding of the interplay among environmental and individual differences on decision-making styles and helps to identify factors of vulnerability for poorer cognitive functioning on stressful scenarios.